Polyoxazoline copolymers containing calcium-binding groups
A polyoxazoline copolymer with calcium binding groups addresses the limitations of current bone repair devices by providing enhanced adhesion and biological integration, improving mechanical properties and reducing reliance on non-degradable materials for bone repair and protection.
Patent Information
- Application Number
- JP2022502464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-30
- Filing Date
- 2020-07-28
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-07-28
AI Technical Summary
Current medical devices for bone repair and protection, such as barrier membranes and fixed devices, face issues with insufficient control over decomposition speed, mechanical properties, biological integration, clinical management, stability, and reliance on non-degradable materials, lacking effective adhesion to bone tissue.
Development of a polyoxazoline copolymer containing calcium binding groups, such as bisphosphonato and EDTA, which forms a hydrogel with high affinity for calcium ions, providing enhanced biological absorption and adhesion to bone tissue, suitable for use in medical products like barrier films, meshes, and bone adhesives.
The polyoxazoline copolymer offers improved biological compatibility and adhesion to bone tissue, enabling effective bone repair and protection with controlled degradation and enhanced mechanical properties, reducing reliance on non-degradable materials.
Smart Images

Figure 0007626404000011 
Figure 0007626404000001 
Figure 0007626404000002
Abstract
Description
Detailed Description of the Invention
[0001] [Field of the Invention] The present invention relates to polyoxazoline copolymers containing one or more calcium-binding groups selected from bisphosphonates, citrates, ethylenediaminetetraacetic acid (EDTA), and combinations thereof.
[0002] The polyoxazoline copolymers of the present invention have a very high affinity for calcium ions and are bioabsorbable.These polyoxazoline copolymers can be advantageously utilized in medical products that are applied onto or into bone tissue to repair and / or protect (damaged) bone.Examples of such medical products include barrier membranes, meshes, patches, tapes, fixation devices, hydrogels, bone adhesives, and nanoparticles.
[0003] [Background of the invention] Barrier membranes are routinely utilized in surgery to allow regeneration of alveolar bone, while various fixation devices are used in general and trauma surgery to fixate soft tissue to bone (tendon rupture), bone to bone (fracture), or foreign implants to bone (hernia repair with mesh).Currently available degradable barrier membranes and fixation devices have significant drawbacks related to i) poor control of degradation rate, ii) poor mechanical properties, iii) poor understanding of the biological mechanisms that determine soft / bone tissue remodeling and infection, iv) poor clinical manageability and stability, and v) long-term reliance on hard, non-degradable materials.
[0004] Currently, biomaterials that specifically adhere to bone are not available. Therefore, the development of medical devices that specifically adhere to bone would solve one of the major problems in oral, general and trauma surgery, namely, easy repair of damaged bone and / or fixation of soft or hard tissue to bone.
[0005] US Patent Application Publication No. 2013 / 0149355 describes a method for preventing protein and cell adsorption, comprising: a) providing a water soluble polymer that includes a hydroxyapatite targeting moiety at one end; b) combining the water-soluble polymer from step (a) with the hydroxyapatite or calcium phosphate coated prosthetic or drug delivery device or surface under conditions effective to promote bonding therewith to form a polymeric construct; c) administering the polymer structure to a bone-containing mammal. The hydroxyapatite targeting moiety can be selected from the group consisting of tetracycline, calcein, bisphosphonate, polyaspartic acid, polyglutamic acid, and aminophosphoric acid. The water-soluble polymer can be selected from the group consisting of poly(alkylene glycol), poly(oxyethylated polyol), poly(olefin alcohol), poly(vinylpyrrolidone), poly(hydroxypropylmethacrylamide), poly(α-hydroxy acid), poly(vinyl alcohol), polyphosphazene, polyoxazoline, and copolymers and terpolymers thereof.
[0006] Lopez-Perez et al. (Self-healing hydrogels formed by complexation between calcium ions and bisphosphonate-functionalized star-shaped polymers, Macromolecules. (2017); 50(21): pp. 8698-8706) described how star-shaped poly(ethylene glycol) (PEG) chain ends were functionalized with alendronate to create a transient network with reversible crosslinking upon addition of calcium ions. The gelling ability of alendronate-functionalized PEG was highly dependent on the number of arms and the molecular weight of the arms. After mixing of the polymer and calcium solutions, the formed hydrogels could be cut and then reverted without a visible interface. Oscillatory rheology showed that the hydrogels recovered 70-100% of their original storage and loss moduli after rupture. Frequency sweep measurements showed liquid-like behavior at low frequencies and solid-like behavior at high frequencies.
[0007] Ossipov (Bisphosphonate-modified biomaterials for drug delivery and bone tissue engineering, Expert Opin Drug Deliv. (2015);12(9):1443-1458) reports that a strategy for chemical immobilization of bisphosphonates in hydrogels and nanocomposites for bone tissue engineering has been uncovered, opening up new applications of bisphosphonates in bone tissue engineering. Conjugates of bisphosphonates with various drug molecules, imaging agents, proteins, and polymers are described in terms of specific targeting to bone and induced therapeutic effects. The conversion of these complexes into hydrogel scaffolds and the application of the resulting materials in bone tissue engineering are also mentioned.
[0008] Wang et al. (The first pamidronate containing polymer and copolymer, Chemical Communications (2006); 26, pp. 2795-2797) describe the synthesis of poly(N-acryloylpamidronate-co-N-isopropylacrylamide).
[0009] Zhang et al. (The interaction of cationic polymers and their bisphosphonate derivatives with hydroxyapatite, Macromol Biosci. (2007);7(5), pp. 656-670) described the construction of polymer linkers containing multiple copies of BP for protein conjugation and targeting to bone. Utilizing poly(L-lysine) (PLL) and poly(ethyleneimine) (PEI) as the polymer backbone, BP, i.e., 2-(3-mercaptopropylsulfanyl)-ethyl-1,1-bisphosphonic acid (thiol BP), was incorporated by using N-hydroxysuccinimidyl polyethylene glycol maleimide and succinimidyl-4-(N-maleimidomethyl)-cyclohexane-1-carboxylate, respectively. The in vitro and in vivo mineral affinities of the polymer-BP complexes were determined in comparison to the unmodified polymer. In vitro results suggested that the cationic polymers bound strongly to HA in the unmodified form. Conjugation of BP did not increase the inherent mineral affinity of the polymer, in contrast, certain modifications adversely affected the binding of the polymer to HA. In vivo results from a rat subcutaneous implant model also showed no significant difference in the mineral affinity of BP-modified and unmodified PEI.
[0010] [Summary of the invention] The present inventors have developed a novel biocompatible polymer that exhibits a very high affinity for calcium ions. The polymer of the present invention is a polyoxazoline (POx) copolymer that contains at least 20 oxazoline units, including at least 4 non-terminal oxazoline units that contain calcium-binding groups selected from bisphosphonate, citrate, ethylenediaminetetraacetic acid (EDTA), and combinations thereof.
[0011] The POx copolymer of the present invention is 2+ By reversible cross-linking with ions, hydrogels can be formed. The POx copolymers of the present invention offer the important advantage of being bioabsorbable. By grafting calcium-binding groups onto the backbone of the POx copolymer, the copolymers can obtain very useful bone-adhesive properties.
[0012] Furthermore, POx can be easily derivatized along the entire polymer backbone, not just at the end groups, allowing for easy tuning of the calcium affinity, biodegradability, and hydrogel properties of POx copolymers.
[0013] The POx copolymers of the present invention can be suitably utilized in a variety of biomedical applications, such as barrier membranes, bone fixation devices, bone implants, (injectable) hydrogels, bone adhesives, and nanoparticles. [Brief description of the drawings]
[0014] [Figure 1] Alendronate-functionalized poly(2-oxazoline) was synthesized in five steps as shown in Figure 1 .
[0015] [Detailed Description of the Invention] Accordingly, a first aspect of the present invention relates to a polyoxazoline (POx) copolymer comprising at least 20 oxazoline units, including at least 4 non-terminal oxazoline units containing calcium-binding groups selected from bisphosphonate, citrate, ethylenediaminetetraacetic acid (EDTA), and combinations thereof.
[0016] The term "oxazoline unit," as used herein, refers to a monomer unit contained in a POx copolymer that is derived from oxazoline or a substituted oxazoline.
[0017] The term "calcium binding group" as used herein means a Ca 2+ Refers to a group that can form two or more separate coordinate bonds with an ion.
[0018] The POx copolymer of the present invention preferably comprises at least 30 oxazoline units, more preferably at least 40 oxazoline units, even more preferably 50-400 oxazoline units, and most preferably 60-200 oxazoline units.
[0019] In addition to the oxazoline units, the POx copolymer may also contain other monomer units. The oxazoline units preferably constitute at least 50% by weight, more preferably at least 80% by weight, even more preferably at least 90% by weight, and most preferably at least 95% by weight of the monomer units contained in the POx copolymer of the present invention.
[0020] The POx copolymers of the present invention are preferably linear, ie, unbranched copolymers.
[0021] The POx copolymers of the present invention may be statistical, alternating, gradient, or block copolymers. Preferably, the POx copolymers are statistical or block copolymers. Most preferably, the POx copolymers are statistical copolymers.
[0022] The affinity of the POx copolymer of the present invention for hydroxyapatite depends on the number of calcium-binding groups in the copolymer. Preferably, the copolymer contains at least 6 non-terminal oxazoline units containing calcium-binding groups. More preferably, the copolymer contains at least 8 non-terminal oxazoline units containing calcium-binding groups, and most preferably, at least 10 non-terminal oxazoline units containing calcium-binding groups.
[0023] The oxazoline units containing a calcium-binding group preferably account for 3 to 50% of the monomer units contained in the POx copolymer, more preferably for 4 to 40%, and most preferably for 5 to 35% of the monomer units contained in the POx copolymer.
[0024] According to one particularly preferred embodiment, the POx copolymer is Formula - [N(R a )CH 2 CH 2 ]-; and Formula - [N(R b )CH 2 CH 2 ]- repeating unit B (In the formula, R a CO-(CHR 1 ) t -H, R b CO-(CHR 1 ) t -CONH-R 2 -X-CO-(CHR 3 ) u -CONR 4 -CO-ccr, R 1 is H or optionally substituted C 1~5 represents alkyl; R 2 is optionally replaced by C 1~5 represents alkylene; R 3 is H or optionally substituted C 1~5represents alkyl; R 4 is H or CH 3 represents; X is O, NR 11 , S, or + NR 11 (R 12 ) ; R 11 and R 12 represents H, methyl, or ethyl; t represents 1, 2, or 3; u represents 1, 2, or 3; ccr stands for calcium binding group) Includes.
[0025] In a preferred embodiment, the calcium binding group (ccr in the formula representing the repeat unit B) represents a bisphosphonate-containing group. Even more preferably, the calcium binding group (ccr) represents a bisphosphonate-containing group of formula (I): -(L)C(Z)(PO 3 H 2 ) 2 (I) or a pharma- ceutically acceptable salt thereof (In the formula, L is an optionally substituted C 1~5 represents alkylene; Z represents H, OH, Cl, F, or a methyl group. Represents.
[0026] In the above formula (I), L is preferably C 2~4 Most preferably, L represents propylene.
[0027] In formula (I), Z preferably represents H, OH or a methyl group, most preferably Z represents OH.
[0028] It has been found that the hydrogel-forming properties of the POx copolymers of the invention can be improved by incorporating oxazoline units carrying carboxylate groups. Thus, according to one particularly preferred embodiment, the copolymer comprises: Formula - [N(R c )CH 2 CH 2 ]- repeating unit C (In the formula, R c CO-(CHR 1 ) t -CONH-R 2 -X-CO-R 5 -cbx, R 5 is optionally replaced by C 1~5 represents alkylene, cbx represents a carboxylate-containing group; R 1 , R 2 , t, and X have the same meanings as previously described herein. Further includes:
[0029] Preferably, cbx in the formula of the repeating unit C is COOH or COO - M + where M is a monovalent metal cation or NH 4 + Most preferably, cbx represents COOH, COO - Na + , or COO - K + Represents.
[0030] The properties of the POx copolymers of the present invention can also be manipulated in a convenient manner by incorporating oxazoline units which affect the polarity of the copolymer. Thus, preferably, the POx copolymer comprises: Formula - [N(R d )CH 2 CH 2 ]- repeating unit D (In the formula, R d CO-(CHR 1 ) t -CONH-R 2 -XR 6 and; R 6 represents H, methyl, or ethyl; R 1 , R 2 , t, and X have the same meanings as previously described herein. Further includes:
[0031] The POx copolymer may advantageously comprise an oxazoline unit carrying a group that confers collagen adhesiveness to the copolymer. Thus, a POx copolymer may be provided that has an affinity for both the inorganic and organic components of bone tissue. Collagen adhesiveness may be imparted by an oxazoline unit carrying an N-hydroxysuccinimidyl group. Thus, in one particularly preferred embodiment, the POx copolymer comprises: Formula - [N(R e )CH 2 CH 2 ]- repeat unit E (In the formula, R e CO-(CHR 1 ) t -CONH-R 2 -X-CO-R 5 -CO-nhs, nhs represents an N-hydroxysuccinimidyl group; R 1 , R 2 , R 5 , t, and X have the same meaning as above. Further includes:
[0032] The properties of the POx copolymer can be further tailored by the presence of oxazoline units that do not carry pendant groups. Thus, in another preferred embodiment, the POx copolymer comprises: Formula - [NHCH 2 CH 2 ]- repeating unit F Further includes:
[0033] According to a preferred embodiment, R in the above formula of repeat units A, B, C and D 1 represents H.
[0034] The integer t in the formulas of repeat units A, B, C and D is preferably 2 or 3.
[0035] In the formulas of repeat units B, C, and D, R 2 preferably represents ethylene.
[0036] The integer u in the formula of repeat unit B is preferably 2 or 3.
[0037] R in the formula of repeating unit B 3 preferably represents H.
[0038] R in the formula of repeating unit B 4 preferably represents H.
[0039] In the formulae of repeat units B, C and D, X preferably represents O.
[0040] R in the formula of repeating unit C 5 preferably represents ethylene.
[0041] R in the formula of repeating unit D 6 preferably represents H.
[0042] According to one particularly preferred embodiment, the POx copolymer of the present invention has the following monomer composition: 40-97mol% of repeat unit A 3 to 50 mol% of repeating unit B 0-40mol% of repeating unit C 0-50mol% of repeating unit D 0-10mol% of repeating unit E 0-10 mol% of repeat unit F.
[0043] Even more preferably, the POx copolymer has the following composition: 50-95mol% of repeating unit A 4 to 40 mol% of repeating unit B 0.3 to 35 mol% of repeating unit C 0-45mol% of repeating unit D 0-8mol% of repeat unit E 0-8 mol% of repeat unit F.
[0044] Most preferably, the POx copolymer has the following composition: 55-92mol% of repeating unit A 5-35mol% of repeating unit B 0.5-32mol% of repeating unit C 0-30mol% of repeating unit D 0-5mol% of repeat unit E 0-5 mol% of repeat unit F.
[0045] Repeat units A and B together preferably constitute at least 55%, more preferably at least 65%, and most preferably at least 70% of the monomer units present in the POx copolymer.
[0046] Repeat units A, B, C, D, and E together preferably constitute at least 60%, more preferably at least 80%, and most preferably at least 90% of the monomer units present in the POx copolymer.
[0047] The total number of repeating units A, B, C, D, and E in the copolymer is preferably in the range of 40 to 200, more preferably in the range of 60 to 150.
[0048] Another aspect of the invention relates to the use of the POx copolymers of the invention to impart bone adhesion to medical products.
[0049] Yet another aspect of the present invention relates to biocompatible medical products containing the POx copolymers of the present invention.
[0050] Examples of medical products in which POx copolymers can be utilized include barrier membranes, meshes, patches, tapes, bone fixation devices, bone implants, hydrogels, bone adhesives, and therapeutic nanoparticles.
[0051] In one embodiment of the present invention, the medical product is not a hemostatic product, such as a hemostatic patch, and does not include oxidized regenerated cellulose.
[0052] Yet another aspect of the present invention is a method for preparing a POx copolymer as described hereinbefore, comprising the steps of: (a) cationic ring-opening polymerization of a mixture containing 2-oxazoline monomers A and B: [ka] (In the formula, R 1 and t have the same meaning as described in claim 1; R 11 is optionally replaced by C 1~5 (representing alkyl) (b) amidating at least some of the alkyl carboxy groups of the intermediate polyoxazoline copolymer by replacing said groups with the formula: 2 NR 2 -XH(wherein, R 2 and X has the same meaning as previously described herein), (c) functionalizing at least some of the amidated groups by reacting said groups with succinic anhydride; (d) activating at least some of the functionalized groups by reacting said groups with N-hydroxysuccinimide; (e) introducing calcium sequestering functionality by reacting at least some of the activated groups with a reactant that contains a calcium binding group; The present invention relates to a method comprising the steps of:
[0053] According to a preferred embodiment, R in the oxazoline monomer B 11 represents methyl.
[0054] Preferably, the calcium-binding functionality is introduced by reacting the activated group with a calcium-binding agent, more preferably a calcium-binding agent selected from bisphosphonates, citrates, and EDTA. Most preferably, the calcium-binding functionality is introduced by reacting the activated group with alendronate or pamidronate.
[0055] After polymerization, the 2-oxazoline monomer A forms the aforementioned oxazoline unit A in the POx copolymer.
[0056] Oxazoline unit B is formed in the final step of the process, i.e. step (e). Oxazoline unit (C) is formed in step (c). Oxazoline unit (D) is formed in step (b). Oxazoline unit (E) is formed in step (d).
[0057] It will be appreciated that the percentage of oxazoline units B, C, D, and E in the final POx copolymer can be manipulated by controlling the level of derivatization in each of steps (b), (c), (d), and (e).
[0058] The oxazoline unit F can be formed by hydrolyzing the polyoxazoline copolymer formed after any one of steps (a) to (e). Preferably, the hydrolysis is carried out between steps (a) and (b).
[0059] The invention is further illustrated by the following non-limiting examples. EXAMPLES
[0060] (material) 2-Ethyl-2-oxazoline (EtOx) was obtained from Sigma-Aldrich. 2-n-Propyl-2-oxazoline (PropOx) was synthesized as described by Hoogenboom et al. (Microwave-assisted synthesis and properties of a series of poly(2-alkyl-2-oxazoline)s, Des. Monomers Polym. (2005), 8, 659-671). 2-Methoxycarbonylethyl-2-oxazoline (MestOx) was synthesized as described by Bouten et al. (Accelerated living cationic ring-opening polymerization of a methyl ester functionalized 2-oxazoline monomer, Polym. Chem. (2015) 6, 514-518). Acetonitrile and tetrahydrofuran were dispensed under a nitrogen atmosphere using an MBraun MB SPS-800 solvent dispersion system. Anhydrous dichloromethane (DCM), anhydrous diethyl ether, HPLC grade methanol, and molten calcium chloride were obtained from Fisher Scientific. Anhydrous N,N-dimethylformamide (DMF) was obtained from Acros Organics. Dowex® 50WX4 100-200(H) and succinic anhydride were obtained from Alfa Aesar. N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), 4-dimethylaminopyridine (DMAP), N,N'-diisopropylcarbodiimide (DIC), N-hydroxysuccinimide (NHS), and alendronate sodium trihydrate (Ale) were obtained from Fluorochem. Dimethylsulfoxide, 2-ethanolamine, methyl-p-toluenesulfonate (MeOTs), and α-cyano-4-hydroxycinnamic acid (CHCA) were obtained from Sigma-Aldrich. Deuterated solvents such as heavy water, chloroform-d, and dimethylsulfoxide-d6 were obtained from Cambridge Isotope Laboratories and Sigma Aldrich. Ultra-high purity Milli-Q water set at 18.2 MΩ / cm was obtained from a WaterPro PS polisher (Labconco, Kansas City, MO). Dialysis membrane Spectra / Por® 3 (3.5 kD cutoff) was obtained from VWR International. The phosphate-buffered saline (PBS) solution contains 2.7 mM KCl, 137 mM NaCl, 2 mM KH 2 PO 4 , and 8 mM Na 2 HPO 4 (pH=7.4). Polyvinylpyrrolidone K90 (PVP) was obtained from Sigma-Aldrich. Poly(2-ethyl-2-oxazoline), average Mw ∼50,000, PDI 3–4, was obtained from Sigma-Aldrich. Pluronic (Kolliphor® P188 / Lutrol-F68) was obtained from BASF. Hydroxyapatite (calcium phosphate, CaP) was obtained from Merck.
[0061] (Synthesis of alendronate-functionalized poly(2-oxazoline)) Alendronate-functionalized poly(2-oxazoline) was synthesized in five steps as shown in Figure 1 .
[0062] 2-Methoxycarbonylethyl-2-oxazoline (MestOx) was copolymerized with 2-ethyl-2-oxazoline (EtOx) or n-propyl-2-oxazoline (PropOx) to obtain randomly distributed statistical copolymers with different polarities. Methyl-p-toluenesulfonate (1 eq), EtOx (m eq) or PropOx (m eq), MestOx (n eq), and dry acetonitrile (4 M) were mixed in the desired ratio in a microwave vial under inert atmosphere. Following the cationic ring-opening mechanism (CROP), polymerization was carried out under microwave irradiation at 140 °C for 15 min. After polymerization, the reaction was quenched by adding ethanolamine (10 eq) at room temperature with stirring for 30 min. The solvent was then evaporated under vacuum to obtain copolymers P1a-P5a of P(EtOx-ran-MestOx) or P(PropOx-ran-MestOx).
[0063] MestOx copolymers P1a-P5a (1 equiv.) were modified by direct amidation with 2-ethanolamine (3.5 equiv.) at 60 °C under reduced pressure (300 mbar) for 16 h. The crude mixture was then purified by three successive precipitations into a mixture of acetone:ether (3:1 (v / v)), redissolved in DCM:MeOH (8:2 (v / v)), followed by ion-exchange chromatography with MeOH. Finally, the solvent was evaporated under vacuum to obtain copolymers P1b-P5b of P(EtOx-OH) or P(PropOx-OH) in the desired ratios.
[0064] These hydroxyl-side functionalized polymers P1b-P5b (1 equiv.) were fully or partially converted to carboxylic acid moieties using succinic anhydride (1.1 equiv.), 4-dimethylaminopyridine (DMAP) (1.1 equiv.) and dissolved in DCM:DMF (9:1 (v / v)) (2 M) for 16 h under argon atmosphere. The crude mixtures were purified by three successive precipitations into acetone, redissolved in DCM:MeOH (8:2 (v / v)), followed by ion-exchange chromatography with MeOH. Finally, the solvent was evaporated under vacuum to give P(EtOx / PropOx-COOH) or P(EtOx / PropOx-OH-COOH) P1c-P9c in the desired ratios.
[0065] These carboxylate-side functionalized copolymers were subsequently modified to reactive esters by carbodiimide coupling with N-hydroxysuccinimide. The functionalized polymers were dissolved in DCM:DMF (95:5 (v / v)) (0.2 M), N-hydroxysuccinimide (1.1 equiv.) and N,N'-diisopropylcarbodiimide (1.2 equiv.) were added as coupling agents, and stirred at room temperature under argon atmosphere for 16 h. They were precipitated twice into acetone:ether (1:1 (v / v)), followed by further precipitation into ether and purified by redissolution in DCM. Finally, the solvent was evaporated under vacuum to give P(EtOx / PropOx-OH-NHS) or P(EtOx / PropOx-NHS) of P1d–P9d.
[0066] The alendronate moiety was incorporated into the polymer side chains via an amidation reaction. NHS-activated copolymers P1d-P9d (1 equiv.) were slowly added to a solution containing alendronate sodium trihydrate (2 equiv.), N-hydroxysuccinimide (1 equiv.), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (1 equiv.) in phosphate-buffered saline (0.5 M), previously pH-adjusted to 7.7 using NaOH and stirred for 4 h at 3 °C. The mixture was then dialyzed for 16 h and subsequently precipitated three times into acetone:ether (3:1 (v / v)) and redissolved in demi-water. Finally, they were freeze-dried to obtain copolymers P1e-P13e of P(EtOx / PropOx-Ale), P(EtOx / PropOx-OH-Ale), or P(EtOx / PropOx-COOH-Ale) in the desired ratios.
[0067] [Example 1] (P(EtOx 90 -Ale 10 ) - Synthesis of P1e) 〔P(EtOx 90 -MestOx 10 ) P1a Following the general procedure, the reaction of a solution of methyl tosylate (0.68 mL, 4.52 mmol), 2-ethyl-2-oxazoline (41.04 mL, 406.59 mmol), and 2-methoxycarbonylethyl-2-oxazoline (6.23 mL, 45.18 mmol) in dry acetonitrile (68 mL, 4 M) was quenched by the addition of 2-ethanolamine (2.72 mL, 45.18 mmol) to give the desired polymer P1a (52.12 g, 4.39 mmol). 1 H NMR [400 MHz, δ (ppm), CDCl 3 ]: 3.63 (br, 3H, 5-CH 3 ), 3.65-3.35 (br, 8H, 1-CH 2 ), 2.70-2.50 (br, 4H, 4-CH 2 ), 2.50-2.20 (br, 2H, 2-CH 2), 0.95-1.15 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n 90:10. SEC: M n 10.6 kDa, D 1.11. MALDI-TOF: M n 9.7 kDa. Yield: 97%.
[0068] 〔P(EtOx 90 -OH 10 ) P1b] Following the general procedure, P1a (43 g, 4.07 mmol) was reacted with 2-aminoethanol (8.60 mL, 142.40 mmol) to give the desired polymer P1b (38.05 g, 3.50 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 3.65 (br, 2H, 7-CH 2 ), 3.75-3.45 (br, 8H, 1-CH 2 ), 3.35-3.25 (br, 2H, 6-CH 2 ), 2.75-2.60 (br, 2H, 5-CH 2 ), 2.60-2.40 (br, 2H, 4-CH 2 ), 2.45-2.25 (br, 2H, 2-CH 2 ), 1.00-0.80 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n 90:10. MALDI-TOF: M n 10.2 kDa. Yield: 86%.
[0069] 〔P(EtOx 90 -COOH 10 ) P1c Following the general procedure, a solution of P1b (38 g, 3.50 mmol), 4-dimethylaminopyridine (0.86 g, 7.00 mmol), and succinic anhydride (4.20 g, 41.98 mmol) in DCM / ACN (9:1) (27 mL, 2 M) was reacted to give the desired polymer P1c (36.01 g, 3.03 mmol). 1H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.15 (br, 2H, 7-CH 2 ), 3.70-3.40 (br, 10H, 1-CH 2 + 6-CH 2 ), 2.75-2.60 (br, 6H, 5-CH 2 + 8-CH 2 ), 2.60-2.45 (br, 2H, 4-CH 2 ), 2.40-2.25 (br, 2H, 2-CH 2 ), 1.10-0.95 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / o 90:10. MALDI-TOF: M n 11.1 kDa. Yield: 87%.
[0070] 〔P(EtOx 90 -NHS 10 ) P1d Following the general procedure, a solution of P1c (6 g, 0.51 mmol), N-hydroxysuccinimide (0.64 g, 5.57 mmol), and N,N′-diisopropylcarbodiimide (0.94 mL, 6.07 mmol) in DCM / ACN (9:1) (60 mL, 0.2 M) was reacted to give the desired polymer P1d (5.65 g, 0.44 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.00-3.90 (br, 2H, 7-CH 2 ), 3.50-3.10 (br, 10H, 1-CH 2 + 6-CH 2 ), 2.90-2.85 (br, 2H, 8-CH 2 ), 2.75-2.70 (br, 4H, 9-CH 2 ), 2.65-2.60 (br, 2H, 8CH 2 ), 2.60-2.40 (br, 2H, 5-CH 2 ), 2.30-2.10 (br, 4H, 2-CH2 + 4-CH 2 ), 0.85-0.70 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / o 90:10. SEC: M n 11.7 kDa, D 1.25. MALDI-TOF: M n 11.5 kDa. Yield: 87%.
[0071] 〔P(EtOx 90 -Ale 10 ) P1e〕 Following the general procedure, a solution of P1d (5.0 g, 0.39 mmol), alendronate sodium trihydrate (2.53 g, 7.79 mmol), N-hydroxysuccinimide (0.45 g, 3.90 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (0.75 g, 3.90 mmol) in PBS (32 mL, 0.5 M) was reacted to give the desired polymer P1e (1.29 g, 0.09 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.10 (br, 4H, 7-CH 2 ), 3.75-3.40 (br, 16H, 1-CH 2 + 6-CH 2 ), 3.30-3.20 (br, 2H, 9-CH 2 ), 2.75-2.45 (br, 16H, 4-CH 2 + 5-CH 2 + 8-CH 2 ), 2.45-2.20 (br, 2H, 2-CH 2 ), 2.05-1.75 (br, 4H, 10-CH 2 + 11-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.19. Experimentally determined copolymer ratio: m / o / p 90:1:9. MALDI-TOF: Mn 12.0 kDa. Yield: 24%.
[0072] [Example 2] (P(EtOx 80 -Ale 20 ) - Synthesis of P2e) 〔P(EtOx 80 -MestOx 20 ) P2a Following the general procedure, the reaction of a solution of methyl tosylate (0.46 mL, 3.01 mmol), 2-ethyl-2-oxazoline (24.32 mL, 240.94 mmol), and 2-methoxycarbonylethyl-2-oxazoline (8.31 mL, 60.24 mmol) in dry acetonitrile (43 mL, 4 M) was quenched by the addition of 2-ethanolamine (1.82 mL, 30.12 mmol) to give the desired polymer P2a (36.22 g, 2.93 mmol). 1 H NMR [400 MHz, δ (ppm), CDCl 3 ]: 3.65 (br, 3H, 5-CH 3 ), 3.65-3.35 (br, 8H, 1-CH 2 ), 2.75-2.50 (br, 4H, 4-CH 2 ), 2.50-2.20 (br, 2H, 2-CH 2 ), 0.95-1.15 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n 80:20. SEC: M n 9.6 kDa, D: 1.17. MALDI-TOF: M n 9.8 kDa. Yield: 97%.
[0073] 〔P(EtOx 80 -OH 20 ) P2b Following the general procedure, P2a (34 g, 3.05 mmol) was reacted with 2-aminoethanol (12.88 mL, 213.47 mmol) to give the desired polymer P2b (31.46 g, 2.64 mmol). 1H NMR [400 MHz, δ (ppm), D 2 O]: 3.65 (br, 2H, 7-CH 2 ), 3.75-3.45 (br, 8H, 1-CH 2 ), 3.35-3.25 (br, 2H, 6-CH 2 ), 2.80-2.60 (br, 2H, 5-CH 2 ), 2.60-2.50 (br, 2H, 4-CH 2 ), 2.50-2.25 (br, 2H, 2-CH 2 ), 1.00-0.80 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n 80:20. MALDI-TOF: M n 9.9 kDa. Yield: 87%.
[0074] 〔P(EtOx 80 -COOH 20 ) P2c Following the general procedure, a solution of P2b (31 g, 2.64 mmol), 4-dimethylaminopyridine (1.29 g, 10.56 mmol), and succinic anhydride (6.34 g, 63.38 mmol) in DCM / ACN (9:1) (38 mL, 2 M) was reacted to give the desired polymer P2c (29.74 g, 2.18 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.15 (br, 2H, 7-CH 2 ), 3.70-3.40 (br, 10H, 1-CH 2 + 6-CH 2 ), 2.75-2.55 (br, 6H, 5-CH 2 + 8-CH 2 ), 2.50-2.45 (br, 2H, 4-CH 2 ), 2.40-2.25 (br, 2H, 2-CH 2 ), 1.10-0.95 (br, 3H, 3-CH 3). Experimentally determined copolymer ratio: m / o 80:20. MALDI-TOF: M n 11.2 kDa. Yield: 83%.
[0075] 〔P(EtOx 80 -NHS 20 ) P2d Following the general procedure, a solution of P2c (33 g, 2.40 mmol), N-hydroxysuccinimide (6.08 g, 52.87 mmol), and N,N′-diisopropylcarbodiimide (8.93 mL, 57.67 mmol) in DCM / ACN (9:1) (556 mL, 0.2 M) was reacted to give the desired polymer P2d (35.63 g, 2.27 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.00-3.90 (br, 2H, 7-CH 2 ), 3.50-3.10 (br, 10H, 1-CH 2 + 6-CH 2 ), 2.90-2.85 (br, 2H, 8-CH 2 ), 2.75-2.70 (br, 4H, 9-CH 2 ), 2.65-2.60 (br, 2H, 8CH 2 ), 2.60-2.40 (br, 2H, 5-CH 2 ), 2.30-2.10 (br, 4H, 2-CH 2 + 4-CH 2 ), 0.85-0.70 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / o 80:20. SEC: M n 12.6 kDa, D 1.21. MALDI-TOF: M n 13.0 kDa. Yield: 95%.
[0076] 〔P(EtOx 80 -Ale 20 ) P2e〕 Following the general procedure, a solution of P2d (15 g, 0.96 mmol), alendronate sodium trihydrate (12.45 g, 38.28 mmol), N-hydroxysuccinimide (2.20 g, 19.14 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (3.67 g, 19.14 mmol) in PBS (155 mL, 0.5 M) was reacted to give the desired polymer P2e (5.47 g, 0.30 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.10 (br, 4H, 7-CH 2 ), 3.80-3.35 (br, 16H, 1-CH 2 + 6-CH 2 ), 3.30-3.20 (br, 2H, 9-CH 2 ), 2.75-2.45 (br, 16H, 4-CH 2 + 5-CH 2 + 8-CH 2 ), 2.45-2.25 (br, 2H, 2-CH 2 ), 2.05-1.75 (br, 4H, 10-CH 2 + 11-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / o / p 80:1:19. 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.15. MALDI-TOF: M n 15.0 kDa. Yield: 31%.
[0077] [Example 3] (P(EtOx 70 -Ale 30 ) - Synthesis of P3e) 〔P(EtOx 80 -MestOx 20 ) P2a Following the general procedure, the reaction of a solution of methyl tosylate (0.46 mL, 3.01 mmol), 2-ethyl-2-oxazoline (24.32 mL, 240.94 mmol), and 2-methoxycarbonylethyl-2-oxazoline (8.31 mL, 60.24 mmol) in dry acetonitrile (43 mL, 4 M) was quenched by the addition of 2-ethanolamine (1.82 mL, 30.12 mmol) to give the desired polymer P2a (36.22 g, 2.93 mmol). 1 H NMR [400 MHz, δ (ppm), CDCl 3 ]: 3.65 (br, 3H, 5-CH 3 ), 3.65-3.35 (br, 8H, 1-CH 2 ), 2.75-2.50 (br, 4H, 4-CH 2 ), 2.50-2.20 (br, 2H, 2-CH 2 ), 0.95-1.15 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n 80:20. SEC: M n 9.6 kDa, D: 1.17. MALDI-TOF: M n 9.8 kDa. Yield: 97%.
[0078] 〔P(EtOx 70 -OH 30 ) P3b Following the general procedure, P3a (51 g, 4.35 mmol) was reacted with 2-aminoethanol (27.55 mL, 456.55 mmol) to give the desired polymer P3b (43.98 g, 3.49 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 3.66 (br, 2H, 7-CH 2 ), 3.75-3.45 (br, 8H, 1-CH 2 ), 3.35-3.25 (br, 2H, 6-CH 2 ), 2.75-2.60 (br, 2H, 5-CH 2 ), 2.60-2.50 (br, 2H, 4-CH2 ), 2.45-2.25 (br, 2H, 2-CH 2 ), 1.00-0.80 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n 70:30. MALDI-TOF: M n 11.1 kDa. Yield: 80%.
[0079] 〔P(EtOx 70 -COOH 30 ) P3c Following the general procedure, a solution of P3b (10 g, 0.79 mmol), 4-dimethylaminopyridine (0.58 g, 4.76 mmol), and succinic anhydride (2.86 g, 28.54 mmol) in DCM / ACN (9:1) (17 mL, 2 M) was reacted to give the desired polymer P3c (9.85 g, 0.64 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.15 (br, 2H, 7-CH 2 ), 3.80-3.45 (br, 10H, 1-CH 2 + 6-CH 2 ), 2.75-2.60 (br, 6H, 5-CH 2 + 8-CH 2 ), 2.60-2.45 (br, 2H, 4-CH 2 ), 2.40-2.25 (br, 2H, 2-CH 2 ), 1.15-1.00 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / o 70:30. MALDI-TOF: M n 13.5 kDa. Yield: 81%.
[0080] 〔P(EtOx 70 -NHS 30 ) P3d Following the general procedure, a solution of P3c (61 g, 3.91 mmol), N-hydroxysuccinimide (14.85 g, 129.00 mmol), and N,N'-diisopropylcarbodiimide (21.79 mL, 140.72 mmol) in DCM / ACN (9:1) (1346 mL, 0.2 M) was reacted to give the desired polymer P3d (57.06 g, mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.00-3.90 (br, 2H, 7-CH 2 ), 3.50-3.10 (br, 10H, 1-CH 2 + 6-CH 2 ), 2.90-2.85 (br, 2H, 8-CH 2 ), 2.75-2.70 (br, 4H, 9-CH 2 ), 2.65-2.60 (br, 2H, 8CH 2 ), 2.60-2.40 (br, 2H, 5-CH 2 ), 2.30-2.10 (br, 4H, 2-CH 2 + 4-CH 2 ), 0.85-0.70 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / o 70:30. SEC: M n 15.6 kDa, D 1.25. MALDI-TOF: M n 16.9 kDa. Yield: 79%.
[0081] 〔P(EtOx 70 -Ale 30 ) P3e〕 Following the general procedure, a solution of P3d (15 g, 0.81 mmol), alendronate sodium trihydrate (15.80 g, 48.61 mmol), N-hydroxysuccinimide (2.80 g, 24.31 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (4.66 g, 24.31 mmol) in PBS (66 mL, 0.5 M) was reacted to give the desired polymer P3e (5.81 g, 0.26 mmol).1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.10 (br, 4H, 7-CH 2 ), 3.80-3.30 (br, 16H, 1-CH 2 + 6-CH 2 ), 3.25-3.15 (br, 2H, 9-CH 2 ), 2.75-2.45 (br, 16H, 4-CH 2 + 5-CH 2 + 8-CH 2 ), 2.45-2.15 (br, 2H, 2-CH 2 ), 2.15-1.70 (br, 4H, 10-CH 2 + 11-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.25. Experimentally determined copolymer ratio: m / o / p 70:2:28. MALDI-TOF: M n 19.5 kDa. Yield: 32%.
[0082] [Example 4] (P(PropOx 90 -Ale 10 ) - Synthesis of P4e) [P(PropOx 90 -MestOx 10 ) P4a Following the general procedure, the reaction of a solution of methyl tosylate (0.57 mL, 3.76 mmol), n-propyl-2-oxazoline (37.59 mL, 338.82 mmol), and 2-methoxycarbonylethyl-2-oxazoline (5.19 mL, 37.65 mmol) in dry acetonitrile (52 mL, 4 M) was quenched by the addition of 2-ethanolamine (2.72 mL, 37.65 mmol) to give the desired polymer P4a (42.08 g, 3.55 mmol). 1 H NMR [400 MHz, δ (ppm), CDCl3 ]: 3.65 (br, 3H, 6-CH 3 ), 3.65-3.35 (br, 8H, 1-CH 2 ), 2.70-2.50 (br, 4H, 5-CH 2 ), 2.40-2.10 (br, 2H, 2-CH 2 ), 1.70-1.50 (br, 2H, 3-CH 2 ), 1.00-0.80 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n 90:10. SEC: M n 10.2 kDa, D 1.08. MALDI-TOF: M n 10.4 kDa. Yield: 94%.
[0083] [P(PropOx 90 -OH 10 ) P4b Following the general procedure, P4a (42 g, 3.55 mmol) was reacted with 2-aminoethanol (21.43 mL, 354.99 mmol) to give the desired polymer P4b (34.49 g, 2.80 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 3.65 (br, 2H, 8-CH 2 ), 3.75-3.45 (br, 8H, 1-CH 2 ), 3.35-3.30 (br, 2H, 7-CH 2 ), 2.75-2.60 (br, 2H, 6-CH 2 ), 2.60-2.50 (br, 2H, 5-CH 2 ), 2.45-2.25 (br, 2H, 2-CH 2 ), 1.65-1.50 (br, 2H, 3-CH 2 ), 1.00-0.80 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n 90:10. MALDI-TOF: M n 10.7 kDa. Yield: 79%.
[0084] [P(PropOx 90 -COOH 10 ) P4c〕 Following the general procedure, a solution of P4b (28 g, 2.31 mmol), 4-dimethylaminopyridine (0.56 g, 4.62 mmol), and succinic anhydride (2.67 g, 26.7 mmol) in DCM / ACN (9:1) (17 mL, 2 M) was reacted to give the desired polymer P4c (21.20 g, 1.61 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.10-4.00 (br, 2H, 8-CH 2 ), 3.60-3.20 (br, 10H, 1-CH 2 + 7-CH 2 ), 2.65-2.50 (br, 6H, 6-CH 2 + 9-CH 2 ), 2.50-2.30 (br, 2H, 5-CH 2 ), 2.30-2.10 (br, 2H, 2-CH 2 ), 1.55-1.40 (br, 2H, 3-CH 2 ), 1.00-0.80 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / o 90:10. MALDI-TOF: M n 11.5 kDa. Yield: 70%.
[0085] [P(PropOx 90 -NHS 10 ) P4d Following the general procedure, a solution of P4c (20 g, 1.52 mmol), N-hydroxysuccinimide (1.93 g, 16.76 mmol), and N,N′-diisopropylcarbodiimide (2.83 mL, 18.29 mmol) in DCM / ACN (9:1) (180 mL, 0.2 M) was reacted to give the desired polymer P4d (19.88 g, 1.41 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6]: 4.10-4.00 (br, 2H, 8CH 2 ), 3.50-3.30 (br, 10H, 1-CH 2 + 7-CH 2 ), 2.95-2.90 (br, 2H, 9-CH 2 ), 2.75-2.70 (br, 4H, 10-CH 2 ), 2.70-2.65 (br, 2H, 9-CH 2 ), 2.65-2.40 (br, 2H, 6-CH 2 ), 2.35-2.10 (br, 4H, 2-CH 2 + 5-CH 2 ), 1.60-1.40 (br, 2H, 3-CH 2 ), 0.90-0.80 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / o 90:10. SEC: M n 12.2 kDa, D 1.21. MALDI-TOF: M n 12.1 kDa. Yield: 93%.
[0086] [P(PropOx 90 -Ale 10 ) P4e〕 Following the general procedure, a solution of P4d (15 g, 1.06 mmol), alendronate sodium trihydrate (6.92 g, 21.29 mmol), N-hydroxysuccinimide (1.23 g, 10.64 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (2.04 g, 10.64 mmol) in PBS (87 mL, 0.5 M) was reacted to give the desired polymer P4e (6.57 g, 0.43 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.15 (br, 4H, 8-CH 2 ), 3.80-3.30 (br, 16H, 1-CH 2 + 7-CH 2 ), 3.30-3.20 (br, 2H, 10-CH2 ), 2.75-2.45 (br, 16H, 5-CH 2 + 6-CH 2 + 9-CH 2 ), 2.45-2.15 (br, 2H, 2-CH 2 ), 2.05-1.75 (br, 4H, 11-CH 2 + 12-CH 2 ), 1.65-1.45 (br, 2H, 3-CH 2 ), 1.15-0.95 (br, 3H, 4-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.17. Experimentally determined copolymer ratio: m / o / p 90:1:9. MALDI-TOF: M n 12.2 kDa. Yield: 40%.
[0087] [Example 5] (P(PropOx 80 -Ale 20 ) - Synthesis of P5e) [P(PropOx 70 -MestOx 30 ) P5a Following the general procedure, the reaction of a solution of methyl tosylate (0.57 mL, 3.76 mmol), n-propyl-2-oxazoline (29.24 mL, 263.53 mmol), and 2-methoxycarbonylethyl-2-oxazoline (15.57 mL, 112.94 mmol) in dry acetonitrile (50 mL, 4 M) was quenched by the addition of 2-ethanolamine (2.72 mL, 37.65 mmol) to give the desired polymer P5a (46.44 g, 3.62 mmol). 1 H NMR [400 MHz, δ (ppm), CDCl 3 ]: 3.65 (br, 3H, 6-CH 3 ), 3.65-3.30 (br, 8H, 1-CH 2 ), 2.65-2.45 (br, 4H, 5-CH 2), 2.40-2.10 (br, 2H, 2-CH 2 ), 1.70-1.50 (br, 2H, 3-CH 2 ), 1.00-0.80 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n 70:30. SEC: M n 10.1 kDa, D 1.12. MALDI-TOF: M n 10.9 kDa. Yield: 96%.
[0088] [P(PropOx 70 -OH 30 ) P5b Following the general procedure, P5a (46 g, 3.62 mmol) was reacted with 2-aminoethanol (22.93 mL, 379.97 mmol) to give the desired polymer P5b (37.13 g, 2.72 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 3.65 (br, 2H, 8-CH 2 ), 3.75-3.45 (br, 8H, 1-CH 2 ), 3.35-3.20 (br, 2H, 7-CH 2 ), 2.70-2.60 (br, 2H, 6-CH 2 ), 2.60-2.50 (br, 2H, 5-CH 2 ), 2.40-2.15 (br, 2H, 2-CH 2 ), 1.65-1.45 (br, 2H, 3-CH 2 ), 0.9-0.70 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n 70:30. MALDI-TOF: M n 11.6 kDa. Yield: 75%.
[0089] [P(PropOx 70 -COOH 30 ) P5c〕 Following the general procedure, a solution of P5b (34 g, 2.50 mmol), 4-dimethylaminopyridine (1.83 g, 15.01 mmol), and succinic anhydride (9.01 g, 90.03 mmol) in DCM / ACN (9:1) (54 mL, 2 M) was reacted to give the desired polymer P5c (39.91 g, 2.41 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.05-3.85 (br, 2H, 8-CH 2 ), 3.55-3.10 (br, 10H, 1-CH 2 + 7-CH 2 ), 2.65-2.50 (br, 6H, 6-CH 2 + 9-CH 2 ), 2.50-2.30 (br, 2H, 5-CH 2 ), 2.30-2.10 (br, 2H, 2-CH 2 ), 1.55-1.35 (br, 2H, 3-CH 2 ), 0.90-0.75 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / o 70:30. MALDI-TOF: M n 12.1 kDa. Yield: 96%.
[0090] [P(PropOx 70 -NHS 30 ) P5d〕 Following the general procedure, a solution of P5c (28 g, 1.69 mmol), N-hydroxysuccinimide (6.41 g, 55.71 mmol), and N,N′-diisopropylcarbodiimide (9.41 mL, 60.77 mmol) in DCM / ACN (9:1) (581 mL, 0.2 M) was reacted to give the desired polymer P5d (26.28 g, 1.35 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.00-3.90 (br, 2H, 8CH 2 ), 3.50-3.10 (br, 10H, 1-CH 2+ 7-CH 2 ), 2.90-2.85 (br, 2H, 9-CH 2 ), 2.75-2.70 (br, 4H, 10-CH 2 ), 2.65-2.60 (br, 2H, 9-CH 2 ), 2.60-2.40 (br, 2H, 6-CH 2 ), 2.35-2.10 (br, 4H, 2-CH 2 + 5-CH 2 ), 1.65-1.40 (br, 2H, 3-CH 2 ), 0.85-0.70 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / o 90:10. SEC: M n 15.7 kDa, D 1.20. MALDI-TOF: M n 13.7 kDa. Yield: 80%.
[0091] [P(PropOx 70 -Ale 30 ) P5e〕 Following the general procedure, a solution of P5d (8.0 g, 0.41 mmol), alendronate sodium trihydrate (8.00 g, 24.62 mmol), N-hydroxysuccinimide (1.42 g, 12.31 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (2.36 g, 12.31 mmol) in PBS (99 mL, 0.5 M) was reacted to give the desired polymer P5e (2.93 g, 0.13 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.15 (br, 4H, 8-CH 2 ), 3.80-3.30 (br, 16H, 1-CH 2 + 7-CH 2 ), 3.20-3.10 (br, 2H, 10-CH 2 ), 2.75-2.45 (br, 16H, 5-CH 2 + 6-CH 2 + 9-CH2 ), 2.45-2.15 (br, 2H, 2-CH 2 ), 2.05-1.75 (br, 4H, 11-CH 2 + 12-CH 2 ), 1.65-1.45 (br, 2H, 3-CH 2 ), 1.00-0.85 (br, 3H, 4-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.15. Experimentally determined copolymer ratio: m / o / p 70:3:27. MALDI-TOF: M n 17.5 kDa. Yield: 31%.
[0092] [Example 6] (P(EtOx 70 -OH 20 -Ale 10 ) - Synthesis of P6e) 〔P(EtOx 70 -OH 20 -COOH 10 ) P6c〕 Following the general procedure, a solution of P3b (15 g, 1.19 mmol), 4-dimethylaminopyridine (0.29 g, 2.38 mmol), and succinic anhydride (1.43 g, 14.27 mmol) in DCM / ACN (9:1) (9 mL, 2 M) was reacted to give the desired polymer P6c (12.28 g, 0.90 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.15 (br, 2H, 9-CH 2 ), 3.80-3.45 (br, 16H, 1-CH 2 + 7-CH 2 + 8-CH 2 ), 3.35-3.25 (br, 2H, 6-CH 2 ), 2.75-2.60 (br, 8H, 5-CH 2 + 10-CH 2 ), 2.60-2.45 (br, 4H, 4-CH 2), 2.45-2.25 (br, 2H, 2-CH 2 ), 1.15-1.00 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:21:9. MALDI-TOF: M n 12.2 kDa. Yield: 76%.
[0093] 〔P(EtOx 70 -OH 20 -NHS 10 ) P6d〕 Following the general procedure, a solution of P6c (12 g, 0.88 mmol), N-hydroxysuccinimide (1.12 g, 9.70 mmol), and N,N′-diisopropylcarbodiimide (1.64 mL, 10.58 mmol) in DCM / ACN (9:1) (104 mL, 0.2 M) was reacted to give the desired polymer P6d (11.48 g, 0.79 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.25-4.15 (br, 2H, 8CH 2 ), 3.75-3.40 (br, 16H, 1-CH 2 + 6-CH 2 + 7-CH 2 ), 3.35-3.25 (br, 2H, 5-CH 2 ), 3.10-3.00 (br, 2H, 9-CH 2 ), 3.00-2.90 (br, 4H, 10-CH 2 ), 2.90-2.80 (br, 2H, 9-CH 2 ), 2.65-2.45 (br, 8H, 4-CH 2 ), 2.45-2.25 (br, 2H, 2-CH 2 ), 1.10-1.00 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:21:9. SEC: M n 12.7 kDa, D 1.25. MALDI-TOF: M n12.6 kDa. Yield: 89%.
[0094] 〔P(EtOx 70 -OH 20 -Ale 10 ) P6e〕 Following the general procedure, a solution of P6d (12 g, 0.83 mmol), alendronate sodium trihydrate (4.88 g, 15.02 mmol), N-hydroxysuccinimide (0.86 g, 7.51 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (1.44 g, 7.51 mmol) in PBS (62 mL, 0.5 M) was reacted to give the desired polymer P6e (3.41 g, 0.22 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.10 (br, 4H, 8-CH 2 ), 3.80-3.40 (br, 22H, 1-CH 2 + 6-CH 2 + 7-CH 2 ), 3.40-3.30 (br, 2H, 5-CH 2 ), 3.30-3.20 (br, 2H, 10-CH 2 ), 2.75-2.15 (br, 22H, 2-CH 2 + 4-CH 2 + 9-CH 2 ), 2.05-1.75 (br, 4H, 11-CH 2 + 12-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.15. Experimentally determined copolymer ratio: m / n / o / p 70:21:1:8. MALDI-TOF: M n 12.6 kDa. Yield: 26%.
[0095] [Example 7] (P(EtOx 70 -OH10 -Ale 20 ) - Synthesis of P7e) 〔P(EtOx 70 -OH 10 -COOH 20 ) P7c〕 Following the general procedure, a solution of P3b (15 g, 1.19 mmol), 4-dimethylaminopyridine (0.58 g, 4.76 mmol), and succinic anhydride (2.86 g, 28.54 mmol) in DCM / ACN (9:1) (17 mL, 2 M) was reacted to give the desired polymer P7c (17.33 g, 1.19 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.15 (br, 2H, 9-CH 2 ), 3.80-3.45 (br, 16H, 1-CH 2 + 7-CH 2 + 8-CH 2 ), 3.35-3.25 (br, 2H, 6-CH 2 ), 2.75-2.60 (br, 8H, 5-CH 2 + 10-CH 2 ), 2.60-2.45 (br, 4H, 4-CH 2 ), 2.40-2.25 (br, 2H, 2-CH 2 ), 1.15-1.00 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:12:18. MALDI-TOF: M n 12.5 kDa. Yield: 94%.
[0096] 〔P(EtOx 70 -OH 10 -NHS 20 ) P7d〕 Following the general procedure, a solution of P7c (12 g, 0.82 mmol), N-hydroxysuccinimide (2.08 g, 18.07 mmol), and N,N'-diisopropylcarbodiimide (3.05 mL, 19.72 mmol) in DCM / ACN (9:1) (190 mL, 0.2 M) was reacted to give the desired polymer P7d (11.95 g, 0.72 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.15-4.00 (br, 2H, 8CH 2 ), 3.75-3.40 (br, 16H, 1-CH 2 + 6-CH 2 + 7-CH 2 ), 3.35-3.25 (br, 2H, 5-CH 2 ), 3.05-2.95 (br, 2H, 9-CH 2 ), 2.95-2.85 (br, 4H, 10-CH 2 ), 2.85-2.70 (br, 2H, 9-CH 2 ), 2.75-2.65 (br, 8H, 4-CH 2 ), 2.40-2.10 (br, 2H, 2-CH 2 ), 1.05-0.95 (br, 3H, 3-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:12:18. SEC: M n 14.7 kDa, D 1.25. MALDI-TOF: M n 14.4 kDa. Yield: 88%.
[0097] 〔P(EtOx 70 -OH 10 -Ale 20 ) P7e〕 Following the general procedure, a solution of P7d (12 g, 0.74 mmol), alendronate sodium trihydrate (8.69 g, 6.74 mmol), N-hydroxysuccinimide (1.54 g, 13.37 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (2.56 g, 13.37 mmol) in PBS (108 mL, 0.5 M) was reacted to give the desired polymer P7e (4.15 g, 0.23 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.10 (br, 4H, 8-CH 2 ), 3.80-3.40 (br, 22H, 1-CH 2 + 6-CH 2 + 7-CH 2 ), 3.40-3.30 (br, 2H, 5-CH 2 ), 3.30-3.20 (br, 2H, 10-CH 2 ), 2.75-2.15 (br, 22H, 2-CH 2 + 4-CH 2 + 9-CH 2 ), 2.05-1.75 (br, 4H, 11-CH 2 + 12-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.25. Experimentally determined copolymer ratio: m / n / o / p 70:12:2:16. MALDI-TOF: M n 14.6 kDa. Yield: 30%.
[0098] [Example 8] (P(PropOx 70 -OH 20 -Ale 10 ) - Synthesis of P8e) [P(PropOx 70 -OH 20 -COOH 10 ) P8c〕 Following the general procedure, a solution of P5b (13 g, 0.96 mmol), 4-dimethylaminopyridine (0.23 g, 1.91 mmol), and succinic anhydride (1.15 g, 11.47 mmol) in DCM / ACN (9:1) (7 mL, 2 M) was reacted to give the desired polymer P8c (11.62 g, 0.80 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.10-3.90 (br, 2H, 10-CH 2 ), 3.70-3.20 (br, 16H, 1-CH 2 + 8-CH 2 + 9-CH 2 ), 3.15-3.00 (br, 2H, 7-CH 2 ), 2.75-2.60 (br, 8H, 6-CH 2 + 11-CH 2 ), 2.65-2.40 (br, 4H, 5-CH 2 ), 2.40-2.10 (br, 2H, 2-CH 2 ), 1.60-1.35 (br, 2H, 3-CH 2 ), 1.00-0.70 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:20:10. MALDI-TOF: M n 11.5 kDa. Yield: 79%.
[0099] [P(PropOx 70 -OH 20 -NHS 10 ) P8d〕 Following the general procedure, a solution of P8c (20 g, 1.37 mmol), N-hydroxysuccinimide (1.74 g, 15.08 mmol), and N,N'-diisopropylcarbodiimide (2.55 mL, 16.45 mmol) in DCM / ACN (9:1) (162 mL, 0.2 M) was reacted to give the desired polymer P8d (17.41 g, 1.12 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d6 ]: 4.15-4.00 (br, 2H, 9-CH 2 ), 3.55-3.30 (br, 16H, 1-CH 2 + 7-CH 2 + 8-CH 2 ), 3.30-3.20 (br, 2H, 6-CH 2 ), 3.00-2.90 (br, 2H, 10-CH 2 ), 2.85-2.75 (br, 4H, 11-CH 2 ), 2.75-2.65 (br, 2H, 10-CH 2 ), 2.65-2.45 (br, 8H, 5-CH 2 ), 2.35-2.05 (br, 2H, 2-CH 2 ), 1.55-1.30 (br, 2H, 3-CH 2 ), 0.90-0.70 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:20:10. SEC: M n 12.2 kDa, D 1.25. MALDI-TOF: M n 12.1 kDa. Yield: 70%.
[0100] [P(PropOx 70 -OH 20 -Ale 10 ) P8e〕 Following the general procedure, a solution of P8d (7.0 g, 0.45 mmol), alendronate sodium trihydrate (2.93 g, 9.00 mmol), N-hydroxysuccinimide (0.52 g, 4.50 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (0.86 g, 4.50 mmol) in PBS (37 mL, 0.5 M) was reacted to give the desired polymer P8e (2.71 g, 0.16 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.10 (br, 4H, 9-CH 2), 3.80-3.40 (br, 22H, 1-CH 2 + 7-CH 2 + 8-CH 2 ), 3.40-3.30 (br, 2H, 6-CH 2 ), 3.30-3.20 (br, 2 H, 11-CH 2 ), 2.75-2.15 (br, 22H, 2-CH 2 + 5-CH 2 + 10-CH 2 ), 2.05-1.75 (br, 4H, 12-CH 2 + 13-CH 2 ), 1.65-1.45 (br, 2H, 3-CH 2 ), 1.15-0.85 (br, 3H, 4-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.20. Experimentally determined copolymer ratio: m / n / o / p 70:20:1:9. MALDI-TOF: M n 12.5 kDa. Yield: 36%.
[0101] [Example 9] (P(PropOx 70 -OH 10 -Ale 20 ) - Synthesis of P9e) [P(PropOx 70 -OH 10 -COOH 20 ) P9c〕 Following the general procedure, a solution of P5b (38 g, 2.80 mmol), 4-dimethylaminopyridine (1.37 g, 11.18 mmol), and succinic anhydride (6.71 g, 67.08 mmol) in DCM / ACN (9:1) (41 mL, 2 M) was reacted to give the desired polymer P9c (41.10 g, 2.64 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.10-3.90 (br, 2H, 10-CH 2), 3.70-3.20 (br, 16H, 1-CH 2 + 8-CH 2 + 9-CH 2 ), 3.15-3.00 (br, 2H, 7-CH 2 ), 2.65-2.60 (br, 8H, 6-CH 2 + 11-CH 2 ), 2.65-2.40 (br, 4H, 5-CH 2 ), 2.40-2.10 (br, 2H, 2-CH 2 ), 1.60-1.35 (br, 2H, 3-CH 2 ), 1.00-0.70 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:10:20. MALDI-TOF: M n 12.8 kDa. Yield: 94%.
[0102] [P(PropOx 70 -OH 10 -NHS 20 ) P9d〕 Following the general procedure, a solution of P9c (41 g, 2.63 mmol), N-hydroxysuccinimide (6.66 g, 57.86 mmol), and N,N'-diisopropylcarbodiimide (9.77 mL, 63.12 mmol) in DCM / ACN (9:1) (608 mL, 0.2 M) was reacted to give the desired polymer P9d (38.62 g, 2.20 mmol). 1 H NMR [400 MHz, δ (ppm), DMSO-d 6 ]: 4.05-3.90 (br, 2H, 9-CH 2 ), 3.55-3.30 (br, 16H, 1-CH 2 + 7-CH 2 + 8-CH 2 ), 3.30-3.20 (br, 2H, 6-CH 2 ), 3.05-2.95 (br, 2H, 10-CH 2 ), 2.95-2.85 (br, 4H, 11-CH 2), 2.85-2.70 (br, 2H, 10-CH 2 ), 2.70-2.55 (br, 8H, 5-CH 2 ), 2.35-2.05 (br, 2H, 2-CH 2 ), 1.55-1.30 (br, 2H, 3-CH 2 ), 0.90-0.70 (br, 3H, 4-CH 3 ). Experimentally determined copolymer ratio: m / n / o 70:10:20. SEC: M n 14.9 kDa, D 1.21. MALDI-TOF: M n 14.4 kDa. Yield: 84%.
[0103] [P(PropOx 70 -OH 10 -Ale 20 ) P9e〕 Following the general procedure, a solution of P9d (12.5 g, 0.62 mmol), alendronate sodium trihydrate (12.05 g, 37.07 mmol), N-hydroxysuccinimide (2.13 g, 18.54 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (3.55 g, 18.54 mmol) in PBS (150 mL, 0.5 M) was reacted to give the desired polymer P9e (4.82 g, 0.22 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.10 (br, 4H, 9-CH 2 ), 3.80-3.40 (br, 22H, 1-CH 2 + 7-CH 2 + 8-CH 2 ), 3.35-3.30 (br, 2H, 6-CH 2 ), 3.25-3.15 (br, 2H, 11-CH 2 ), 2.75-2.20 (br, 22H, 2-CH 2 + 5-CH 2 + 10-CH 2), 2.05-1.75 (br, 4H, 12-CH 2 + 13-CH 2 ), 1.65-1.45 (br, 2H, 3-CH 2 ), 1.00-0.85 (br, 3H, 4-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.12. Experimentally determined copolymer ratio: m / n / o / p 70:10:3:17. MALDI-TOF: M n 17.9 kDa. Yield: 35%.
[0104] [Example 10] (P(EtOx 70 -COOH 20 -Ale 10 ) - Synthesis of P10e) Following the general procedure, a solution of P3d (15 g, 0.81 mmol), alendronate sodium trihydrate (10.54 g, 32.41 mmol), N-hydroxysuccinimide (1.86 g, 16.20 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (1.86 g, 16.20 mmol) in PBS (131 mL, 0.5 M) was reacted to give the desired polymer P10e (5.22 g, 0.28 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.10 (br, 4H, 6-CH 2 ), 3.80-3.40 (br, 16H, 1-CH 2 + 5-CH 2 ), 3.30-3.20 (br, 2H, 8-CH 2 ), 2.75-2.15 (br, 18H, 2-CH 2 + 4-CH 2 + 7-CH 2 ), 2.05-1.75 (br, 4H, 9-CH 2 + 10-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.18. Experimentally determined copolymer ratio: m / o / p 70:17:13. MALDI-TOF: M n 16.3 kDa. Yield: 34%.
[0105] [Example 11] (P(EtOx 70 -COOH 10 -Ale 20 ) - Synthesis of P11e) Following the general procedure, a solution of P3d (15 g, 0.81 mmol), alendronate sodium trihydrate (10.54 g, 32.41 mmol), N-hydroxysuccinimide (1.86 g, 16.2 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (3.11 g, 16.20 mmol) in PBS (131 mL, 0.5 M) was reacted to give the desired polymer P11e (4.99 g, 0.24 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.25-4.10 (br, 4H, 6-CH 2 ), 3.80-3.40 (br, 16H, 1-CH 2 + 5-CH 2 ), 3.25-3.15 (br, 2H, 8-CH 2 ), 2.75-2.15 (br, 18H, 2-CH 2 + 4-CH 2 + 7-CH 2 ), 2.05-1.70 (br, 4H, 9-CH 2 + 10-CH 2 ), 1.15-0.95 (br, 3H, 3-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.25. Experimentally determined copolymer ratio: m / o / p 70:10:20. MALDI-TOF: M n 16.3 kDa. Yield: 30%.
[0106] [Example 12] (P(PropOx 70 -COOH 20 -Ale 10 ) - Synthesis of P12e) Following the general procedure, a solution of P5d (5.0 g, 0.26 mmol), alendronate sodium trihydrate (1.67 g, 5.13 mmol), N-hydroxysuccinimide (0.30 g, 2.56 mmol), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (0.49 g, 2.56 mmol) in PBS (21 mL, 0.5 M) was reacted to give the desired polymer P12e (2.17 g, 0.12 mmol). 1 H NMR [400 MHz, δ (ppm), D 2 O]: 4.30-4.15 (br, 4H, 7-CH 2 ), 3.80-3.30 (br, 16H, 1-CH 2 + 6-CH 2 ), 3.30-3.20 (br, 2H, 9-CH 2 ), 2.75-2.15 (br, 18H, 2-CH 2 + 5-CH 2 + 8-CH 2 ), 2.05-1.75 (br, 4H, 10-CH 2 + 11-CH 2 ), 1.65-1.45 (br, 2H, 3-CH 3 ), 1.15-0.95 (br, 3H, 4-CH 3 ). 31 P NMR [400 MHz, δ (ppm), D 2 O]: 18.00. Experimentally determined copolymer ratio: m / o / p 70:22:8. MALDI-TOF: M n 14.8 kDa. Yield: 46%.
[0107] [Example 13] Characterization of Alendronate-Functionalized Poly(2-oxazoline) The degree of modification of various substitutions in the polymer 1 The presence of the alendronate moiety was also determined by 1 H NMR. 31 P NMR was used to determine the NMR spectra. NMR spectra were recorded on a Varian Inova400 (400 MHz) or a Bruker Avance III (400 MHz) spectrometer at 25° C. in the indicated solvent. 1 H NMR data are reported as chemical shifts (given in parts per million (ppm) relative to tetramethylsilane as standard), multiplicities (br = broad line), integrals, and assignments. Number average molecular weights (M n ) were recorded on a Bruker Microflex LRF matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) system. All mass spectra were obtained in positive ion mode. α-Cyano-4-hydroxycinnamic acid (CHCA) was used as the matrix in tetrahydrofuran (10 mg / mL). The analyte solutions were prepared by dissolving the polymer samples in THF:methanol (1:1 (volume / volume)) (10 mg / mL) and mixing 10 μL of matrix and 1 μL of polymer sample. The dried droplet method was used to deliver the samples. Size exclusion chromatography (SEC) was performed on a Shimadzu automated HPLC system at 50 °C using a PLgel 5 μm MIXED-D column with N,N-dimethylacetamide (DMA) containing 50 mM LiCl as the eluent at a flow rate of 0.6 mL / min. Polydispersity index values (PDI) were calculated against poly(methyl methacrylate) (PMMA) standards.
[0108] The results of these analyses are summarized in Table 1.
[0109] [Table 1]
[0110] [Example 14] (Isothermal titration calorimetry (ITC)) Isothermal titration calorimetry was used to evaluate the affinity between the synthesized POx-Ale polymers and calcium cations dissolved in water. ITC experiments were performed on a fully automated Microcal Auto-iTC200. Curve fitting was performed with Origin 6.0 using the one set of sites binding model. In general, 0.36 mM per unit of alendronate present in the polymer was titrated with 4 mM CaCl at 20 °C. 2 All polymers were titrated with the same batch of calcium. Each ITC titration consisted of 19 injections. All measurements were performed in triplicate.
[0111] Statistical analysis was performed using GraphPad InStat® software. Rheological results were statistically analyzed using one-way ANOVA test followed by Tukey's multiple comparison test. The significance threshold was set at P<0.05.
[0112] The results of the ICT analysis are summarized in Table 2.
[0113] [Table 2]
[0114] Polymers containing alendronate moieties have a binding constant (K Ca 2+ ) clearly showed a strong interaction with calcium ions. The binding affinity increased linearly with the percentage of alendronate present in the polymer. Furthermore, the binding affinity of the EtOx polymer with Ca 2+ The interaction with CaCl was 1.5 times that of PropOx, which may be due to the higher solubility of EtOx in aqueous solutions. In particular, P(EtOx-Ale) 70-30% exhibited significantly greater interaction with CaCl compared to alginate (140 times) and PEG-Ale polymer (120 times) reported in the literature. 2 It showed improved binding affinity with Fang et al., Multiple Steps and Critical Behaviors of the Binding of Calcium to Alginate, The Journal of Physical Chemistry B 2007, 111(10), pp. 2456-2462. Chu et al., Calcium phosphate nanoparticles functionalized with alendronate-conjugated polyethylene glycol (PEG) for the treatment of bone metastasis, Int J Pharm 2017, 516(1), pp. 352-363.
[0115] [Example 15] (Preparation of calcium cross-linked POx-Ale gel) Equal amounts of POx-Ale in phosphate-buffered saline (PBS) at different polymer concentrations (10, 20, and 30 wt%) and CaCl 2 Gels were prepared by mixing several solutions containing 1, 10, 20, and 40 wt % of 1H2O and 1H2O in a total volume of 200 μL. The mixture was vigorously stirred with a vortex for 15 s to obtain a homogenous gel.
[0116] (Visual Observation of Gelation) Equal amounts of alendronate-functionalized polymer and final polymer concentrations of 10, 20, and 30 wt% were mixed with Ca 2+ Ca concentrations between 1 and 40% by weight 2+ The solution was mixed with the polymer to obtain a viscous solution or a self-healing hydrogel. In general, increasing both the polymer and calcium concentrations resulted in the formation of stronger gels.
[0117] Polymers without alendronate moieties (P(EtOx)) with hydroxyl or carboxylic acid moieties in the side chain 70 -OH 30 ) and P(EtOx 70 -COOH 30 )) did not increase in viscosity or form a gel.
[0118] Visually, two different types of gels were formed. 70 -Ale 30 ) and P(EtOx 70 -COOH 10 -Ale 20 ) produces a white, stable transient network, while P(EtOx 70 -OH 10 -Ale 20 ) formed clear soft gels. When more than 20 mol % alendronate was present in the polymer or when Ca 2+ In the case of those with carboxylic acid moieties that could bind to , the binding affinity was so strong that the gelation process competed with the precipitation of the polymer, which caused the gel to lose transparency.
[0119] Hydrogel (30 wt.% P(EtOx 70 -OH 10 -Ale 20 ) and 20% by weight CaCl 2 The self-healing properties of the gels were visually evaluated. Two gels of the same composition were stained using blue (brilliant) or red (amaranth) dye. The gels were cut in half transversely, and the two stained halves were then brought together without the application of external force. After 2 minutes of contact, no boundary was observed between them, and the joint was strong enough to be pulled.
[0120] (Rheological property evaluation) The rheological properties of the gels were evaluated at 25°C using an AR2000 Advanced Rheometer (TA instruments) in a flat steel plate geometry (8 mm diameter) and an adjusted gap distance of 500 μm. A frequency sweep was performed by varying the angular frequency from 0.1 to 10 Hz at a constant strain of 1%. The storage modulus, loss modulus, and tan(Δ) were determined by performing a time sweep measurement at 1% strain and 1 Hz. The self-repairing ability of the gels was evaluated by performing three consecutive break-recovery tests measuring the recovery rate G' after gel failure, as follows: First, a 10-minute time sweep was performed at 1% strain and 1 Hz to determine the viscoelastic region. The strain was then gradually increased from 1 to 1000% over a period of 3 minutes to ensure the network failure. The strain was then returned to the initial value over a period of 10 minutes, and the recovery rate was calculated using the following equation 1:
number
[0121] It was found that increasing the number of alendronate moieties in the polymer produced gels with increased elasticity, as evidenced by increased values of storage modulus (G') and loss modulus (G"). 90 -Ale 10 ) produced viscous gels, whereas increasing the mol% to 30% produced stable solid-like hydrogels. The storage modulus was increased: i) 60-fold by changing the degree of alendronate substitution from 10% to 20%, and ii) 125-fold by increasing the alendronate content from 20% to 30%.
[0122] The incorporation of carboxylic acid moieties in the side chain was found to have a positive effect on the storage modulus (G').
[0123] All gel compositions exhibited frequency-dependent rheological behavior. In general, gel strength increased with frequency. Only the gel containing 10 mol% alendronate exhibited liquid-like behavior (characterized by a lower storage modulus (G') than loss modulus (G")) at low frequencies and solid-like behavior at high frequencies.
[0124] Three different hydrogels (P(EtOx 70 -Ale 30 ) and P(EtOx 70 -COOH 10 -Ale 20 ) and P(EtOx 70 -OH 10 -Ale 20 The elastic recovery of hydrogels was tested. Increasing the strain from 1% to 1000% in 3 min induced gel destruction, which was evident by a sudden decrease in the storage and loss modulus values. At the initial strain of 1%, a very fast elastic recovery was observed with the storage and loss modulus values. Surprisingly, some hydrogels recovered more than 100% elasticity, which may be due to the higher packing density of the gels after high shear. Hydrogels made with polymers containing hydroxyl moieties showed higher yield strength, which corresponds to increased malleability, while other gels were more brittle.
[0125] (In vitro stability of hydrogel) To study both the stability and reversibility of the formed crosslinks, we immersed the gels in EDTA (100 mM, pH 6) and monitored them for 48 h.
[0126] P(EtOx 70 -OH 10 -Ale 20 ) was completely dissolved in EDTA within 3 hours after immersion, thereby 2+ It was confirmed that the cross-linking between P(EtOx) and alendronate was responsible for network formation. 70 -Ale 30 ) and P(EtOx 70 -COOH 10 -Ale20 ) remained stable even after immersion in EDTA for 48 hours, indicating that the crosslinks were strong enough not to be destroyed by the coupling agent.
[0127] [Example 16] (Preparation of bone and mineral adhesive slurry) Gelatin or cellulose as starting material (50 mg) was mixed with POx-Ale in a 1:1 weight ratio. Some of the formulations contained 10% by weight calcium ions (CaCl 2 ), calcium phosphate particles (CaP), polyvinylpyrrolidone (PVP), or Pluronic® (Lutrol® F-68, BASF). Then, 0.15 mL of Milli-Q water was added to form a slurry.
[0128] The following gelatin or cellulose based starting materials were used: Gelatin powder (Gelita SPON®) Fibrous gelatin carrier (Tuft-it®) Cellulose powder (Gelita-CEL-CA®)
[0129] (Adhesion to bone and mineral substrates) The adhesion of the slurries was evaluated in vitro against calcium phosphate-coated titanium (Ti) plates (CaP-Ti) and cortical bone. The results are summarized in Table 3. Adhesion was scored as follows: 3-Very strong adhesion 2-Strong adhesion 1-Weak adhesion 0 - No adhesion
[0130] [Table 3]
[0131] All POx-alendronate slurries demonstrated adhesion to both bone and CaP-Ti disks. Adhesion to bone and CaP-Ti was stronger for POx-Ale-containing slurries than for the control slurry without POx-Ale. Adhesion of these slurries to bone and CaP-Ti was stronger when CaCl 2 and / or Pluronic / PVP addition did not improve the results.
[0132] These results suggest that adhesion of the above slurries to bone is mediated by POx-conjugated alendronate groups and may be impaired by the presence of soluble calcium ions, which may reduce the amount of alendronate groups available for binding to mineral-bound calcium in bone.
[0133] [Example 17] (Preparation of bone and mineral-adherent patches) Commercially available hemostatic patches (2.5 × 2.5 cm, 60–65 mg) were impregnated with the POx-based polymer by immersing the patches in blue-dyed aqueous solutions of POx-Ale (30 mg POx-Ale per mL for a 1:1 patch / polymer weight ratio or 15 mg POx-Ale per mL for a 1:0.5 patch / polymer weight ratio). Some of the impregnation solutions contained 10 wt% calcium chloride (CaCl 2 ), alendronate, or Pluronic® (Lutrol® F-68, BASF). After impregnation, the patches were lyophilized. A non-impregnated patch was used as a control.
[0134] Subsequently, a backing layer composed of 8 wt % PLGA, 67% PLC, and 25 wt % poly(2-ethyl-2-oxazoline) was adhered to the polymer-impregnated patch using a heating plate (100 °C).
[0135] The following commercially available patches were used: Gelatin foam (Gelita Rapid®, Gelita Medical, Germany) Fibrous cellulose carrier (SURGICEL® SNoW™, Ethicon, USA)
[0136] (Adhesion to bone and mineral substrates) The adhesion properties of the impregnated patches were evaluated in vitro against calcium phosphate coated Ti plates (CaP-Ti) and cortical bone. The results are summarized in Table 4. Adhesion was scored as follows: 3-Very strong adhesion 2-Strong adhesion 1-Weak adhesion 0 - No adhesion
[0137] [Table 4]
[0138] All tested patches showed good flexibility and bending properties. All POx-alendronate containing patches showed higher adhesion to both bone and CaP coated Ti disks compared to the control without POx-alendronate. Prototypes with adhesion scores of 2 or 3 maintained adhesion to bone even after immersion in a water bath (room temperature) for 24 hours.
[0139] [Example 18] Isothermal titration calorimetry (see Example 14) was used to assess the affinity between calcium cations dissolved in water and: P(EtOx 80 -Ale 20 ) Alendronate Monosodium Trihydrate P(EtOx 70 -COOH 30 ) P(EtOx 70 -OH 30 ) P(EtOx) = non-functionalized poly(2-ethyl-2-oxazoline), M w 50kDa, Labshop, Netherlands
[0140] The binding of calcium cations to free alendronate was confirmed by the alendronate groups conjugated to the polymer (K C a 2+ =2.4×10 5 M -1 ), whereas the binding constants for POx-COOH, POx-OH, and P(EtOx) were found to be below the detection limit.
[0141] [Example 19] (Preparation of bone and mineral-adherent patches) The adhesive patch is made of an adhesive polymer (P(EtOx 70 -Ale 30 ) and P(EtOx 70 -OH 10 -Ale 20 )) 5×7cm 2 A control patch without alendronate was prepared by dry-depositing P(EtOx) onto the same fibrous gelatin carrier (Gelita TUFT-IT®, Germany). The control patch without alendronate was prepared by dry-depositing P(EtOx) onto the same fibrous gelatin carrier. The polymer was first ball-milled at 30 Hz for 10 min, followed by sieving to less than 63 μm to produce a fine powder.
[0142] The polymer was then dried using a rotary evaporator at 40° C. and 20 mbar for 16 hours, and the support was dried using a vacuum oven at 40° C. and 5 mbar for 16 hours. The polymer powder was then loaded into the support for 20 seconds using a high-voltage electrostatic impregnation system (Fibroline SL-Preg, France) at 40 kV, 100 Hz with a polymer / support weight ratio of 60%:40% to obtain a uniform distribution of the polymer powder through the gelatin support.
[0143] An occlusive polyester backing layer was attached to the impregnated carrier by two cycles of heating at 100° C. with 30 N compression for 3 seconds, resulting in a final weight ratio of polymer / carrier / backing of 42%:28%:30%. Using a scalpel (carbon steel, blade 20), the patches were cut to the dimensions required for each experiment. For further storage, they were individually placed in aluminum bags and dried at 40° C., 5 mbar for 16 hours. Finally, they were sealed at 2 mbar with a nitrogen flush of 600 mbar for 4 seconds.
[0144] (Preparation of bone samples) Obtain pork ribs and cut them into pieces approximately 2.5 x 0.7 x 1.2 cm using a circular saw. 3 The bones were divided into rectangular pieces of 0.01 mm in diameter and 0.01 mm in length. Each piece was polished (Struers TegraPol 35, USA) at 150 rpm with carbon paper (P500) until the flat surface of the cortical bone was exposed. The specimens were then frozen and stored at -20°C until further use.
[0145] The flat bone specimens were immersed in 500 mL of Sakura TDE™ 30 reagent and decalcified using the Sakura TDE™ 30 electrode system for 24 hours, after which they were stored frozen at −20° C. until further use.
[0146] (Preparation of apatite-coated titanium plates) Commercially available pure titanium plate (2.5 x 0.1 x 2.5 cm 3 , Grade 2) is first grit blasted to an average roughness R of 1.5 μm a These substrates were then ultrasonically cleaned for 20 min in Milli-Q water, followed by isopropanol. The substrates were then placed on a rotating holder and etched with argon plasma for 10 min, after which they were sputtered by a high-frequency magnetron sputtering system (Edwards ESM 100) at a power of 400 W and 5 × 10 -3A thin adherent coating of hydroxyapatite was physically vapour deposited for 12 h at 100 mbar argon pressure. After deposition, the hydroxyapatite-coated plate was crystallised by heat treatment in a furnace at 650 °C for 2 h with heating and cooling rates of 1.5 °C / min, resulting in a 1 μm apatitic calcium phosphate coating.
[0147] (Tensile test) Tensile tests were performed using a tensile bench (LS5, Lloyd Instruments, UK) equipped with a 100N load cell. All measurements were performed in sextuplicates (n=6). Patches were 1.5×2.5cm 2 The patches were cut into pieces of (length x height). Each end of the patch was clamped in a tensile grip and the patch was subsequently tested in the dry state until failure at a crosshead displacement rate of 1 mm / min. The tensile force was recorded as a function of displacement and the tensile force vs. patch elongation was automatically acquired. The tensile strength was calculated as the maximum load before the sample broke divided by the cross-sectional area of the sample. The tensile modulus of the patch was calculated as the average slope of the initial linear portion of the stress-strain curve.
[0148] The tensile strength and modulus of elasticity of the various patches are shown in Table 5.
[0149] [Table 5]
[0150] These patches were further strengthened by applying hydroxyl-functionalized POx polymers to patches composed of fibrous gelatin and polyester backing. This phenomenon can be attributed to interactions between the hydroxyl groups of the polyoxazoline and the amine and carboxylic acid groups present in the carrier, as well as with the amines present in the backing layer.
[0151] (Lap-shear adhesion test to mineral, non-mineral substrate, bone, and demineralized bone specimens) Lap shear adhesion tests were performed using a tensile bench (LS5, Lloyd Instruments, UK) equipped with a 100N load cell. All measurements were performed in sextuplicates (n=6). To measure adhesion to apatite-coated substrates, patches were applied in 1.5×2.5 cm 2 Due to the small size of the bone samples, the patches were cut into 1.5 × 1.0 cm pieces for bone adhesion testing. 2 Uncoated titanium and demineralized bone specimens were used as control model surfaces.
[0152] The patch was glued to a plastic holder. The substrate was then moistened with gauze soaked in PBS, and the patch was then adhered to the substrate with a controlled force of 10 N for 5 min. Lap shear adhesion tests were then performed at a crosshead displacement rate of 0.5 mm / min. The shear strength was measured by measuring the maximum load before failure at 3.75 cm for the Ti plate and 1.25 cm for the Ti plate. 2 and 1.5 cm for bone specimens. 2 The tensile modulus of the patch was calculated as the average slope of the initial linear portion of the stress-strain curve.
[0153] The results of the lap shear adhesion measurements are summarized in Table 6.
[0154] [Table 6]
[0155] The polymer with the highest number of alendronate moieties (P(EtOx 70 -Ale 30 )) adhered 41 times better to CaP-coated Ti plates and 18 times better to bone than Bio-Guide®, a barrier film widely used in dental applications.
[0156] (Underwater adhesion test to bone) 1cm 2The patches were attached to the bone specimens for 5 minutes. They were then immersed in 200 mL of water, stirred at 150 rpm, and monitored for 24 hours to assess their attachment and swelling. Experiments were performed in triplicate.
[0157] The results are summarized in Table 7. The degree of swelling was scored as follows: 3=High swelling 2 = Medium swelling 1=Low swelling
[0158] The degree of adhesion was scored as follows: -= No patches attached + / - = Poor adhesion +=Good adhesion ++ = Excellent adhesion on all three patches
[0159] [Table 7]
[0160] Only the patches containing POx-alendronate remained attached to the bone after 24 hours of immersion in water, and these patches also swelled less than the other patches.
Claims
1. A polyoxazoline copolymer comprising at least 20 oxazoline units, including at least 4 non-terminal oxazoline units containing calcium-binding groups, comprising: The polyoxazoline copolymer is A repeat unit A of the formula -[N(R a )CH 2 CH 2 ]-; and Repeating unit B of formula -[N(R b )CH 2 CH 2 ]- (In the formula, R a is CO—(CHR 1 ) t —H; R b is CO—(CHR 1 ) t —CONH—R 2 —X—CO—(CHR 3 ) u —CONR 4 —CO-ccr; R 1 represents H or optionally substituted C 1-5 alkyl; R 2 represents an optionally substituted C 1-5 alkylene; R 3 represents H or optionally substituted C 1-5 alkyl; R 4 represents H or CH 3 ; X represents O, NR 11 , S, or +NR 11 (R 12 ); R 11 and R 12 represent H, methyl, or ethyl; t represents 1, 2, or 3; u represents 1, 2, or 3; ccr represents the calcium binding group. Including, A polyoxazoline copolymer, wherein the calcium binding group is a bisphosphonate.
2. A polyoxazoline copolymer as described in claim 1, wherein the oxazoline units containing the calcium binding group account for 3 to 50% of the monomer units contained in the POx copolymer.
3. Formula - [N(R c ) CH 2 CH 2 ]-repeating unit C (In the formula, R c CO-(CHR 1 ) t -CONH-R 2 -X-C-O-R 5 -cbx, R 5 is an optionally substituted C 1~5 represents alkylene, cbx represents a carboxylate-containing group; R 1 , R 2 , t and X have the same meanings as in claim 1.
2. The polyoxazoline copolymer of claim 1, further comprising:
4. cbx is COOH or COO - M + where M is a monovalent metal cation or NH 4 + 4. The polyoxazoline copolymer of claim 3, wherein
5. Formula - [N(R d ) CH 2 CH 2 ]-repeating unit D (In the formula, R d CO-(CHR 1 ) t -CONH-R 2 -X-R 6 and R 6 represents H, methyl or ethyl; R 1 , R 2 , t and X have the same meanings as described in claims 1 and 3. The polyoxazoline copolymer of any one of claims 1 to 4, further comprising:
6. Formula - [N(R e ) CH 2 CH 2 ]-repeating unit E (In the formula, R e CO-(CHR 1 ) t -CONH-R 2 -X-C-O-R 5 -CO-nhs, nhs represents an N-hydroxysuccinimidyl group; R 1 , R 2 , R 5 , t and X have the same meanings as described in claims 1 and 3. The polyoxazoline copolymer of any one of claims 1 to 5, further comprising:
7. Formula - [NHCH 2 CH 2 ]-repeating unit F The polyoxazoline copolymer of any one of claims 1 to 6, further comprising:
8. R 1 A polyoxazoline copolymer according to any one of claims 1 to 7, wherein represents H.
9. A polyoxazoline copolymer according to any one of claims 1 to 8, wherein X represents O.
10. 10. The polyoxazoline copolymer of claim 1, wherein the total number of repeat units A, B, C, D, and E in the copolymer is in the range of 60 to 200.
11. Use of a polyoxazoline copolymer according to any one of claims 1 to 10 for imparting bone-adhesive properties to a medical product.
12. A biocompatible medical product containing the polyoxazoline copolymer according to any one of claims 1 to 10.
13. (a) cationic ring-opening polymerization of a mixture comprising 2-oxazoline monomers A and B: 【Chemistry 1】 (In the formula, R 1 and t have the same meaning as in claim 1; R 11 is an optionally substituted C 1~5 represents alkyl) (b) amidating at least some of the alkyl carboxy groups of the intermediate polyoxazoline copolymer by converting said alkyl carboxy groups to a compound of the formula: 2 N-R 2 -X-H (wherein, R 2 and X has the same meaning as in claim 1), (c) functionalizing at least some of the amidated groups by reacting the amidated groups with succinic anhydride; (d) activating at least some of the functionalized groups by reacting the functionalized groups with N-hydroxysuccinimide; (e) introducing calcium sequestering functionality by reacting at least some of the activated groups with a reactant that contains the calcium-binding group; A method for preparing the polyoxazoline copolymer of any one of claims 1 to 10, comprising:
Citation Information
Patent Citations
Hydroxyapatite-targeted poly(ethylene glycol) and related polymers
JP2004522712A
Beneficial Agent Delivery Composition
JP2010516862A
Electrophilically activated polyoxazoline-derived crosslinked polymers and implants
JP2014503017A
Polyoxazoline polymers and methods for producing them, conjugates of these polymers and their medical uses
JP2015503556A
Targeted polymeric conjugates and uses thereof
US20140271483A1